Pioneering Carbon Recapture for a Greener Planet - Kumar, Anil (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 11 No 3&4 (2024): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2024)
This research paper explores a diverse portfolio of constructive ideas and strategies aimed at mitigating atmospheric CO2 concentrations to safer levels. Focused on the utilization of both live and dead trees, the proposed techniques involve harvesting through collection and selective cutting strategies to recapture and lock up carbon. Mature trees, which exhibit reduced growth and biomass formation compared to their infancy, provide an opportunity to preserve heavy wood logs either by depositing them in trenches or utilizing them as construction materials. The preservation of these logs in a largely anaerobic environment, created by a sufficiently thick layer of soil, prevents the decomposition of buried wood. By interrupting the return pathway of assimilated CO2 to the atmosphere, this approach establishes an effective carbon sink. This not only aids in reversing dangerous atmospheric CO2 levels but also offers additional advantages, such as minimizing CO2 emissions from deforestation, extending the lifetime of reforestation carbon sinks, and reducing the risk of wildfires. While burying wood as a carbon sequestration method holds promise, there are potential environmental impacts, such as nutrient lock-up. Despite appearing manageable, it is essential to acknowledge that certain concerns and factors may limit the realization of the full potential of this approach. Further research and consideration of these limitations will be crucial in developing sustainable and effective carbon sequestration strategies.